Ethynylene-linked multifunctional benzoxazines: the effect of the ethynylene group and packing on thermal behavior. Issue 39 (7th September 2022) - Muraoka, Masanobu; Goto, Masahide; Minami, Masaki; Zhou, Dayang; Suzuki, Takeyuki; Yajima, Tatsuo; Hayashi, Jun'ichi; Sogawa, Hiromitsu; Sanda, Fumio
Abstract : The cured resins of ethynylene-linked mono-, di- and tri-functional benzoxazines were thermally more stable than the resins obtained from the analogous benzoxazines without a triple bond. Abstract : Benzoxazine is a promising next-generation thermosetting resin featuring catalyst-free curing, high thermal stability, and low volume shrinkage upon curing. Mono-, di- and tri-functional benzoxazines, 3-(4-(phenylethynyl)phenyl)-3, 4-dihydro-2 H -[1, 3]benzoxazine (1 ), 1, 4-bis((4-(2 H -3(4 H )-[1, 3]benzoxazinyl)phenyl)ethynyl)benzene (2 ) and 1, 3, 5-tris((4-(2 H -3(4 H )-[1, 3]benzoxazinyl)phenyl)ethynyl)benzene (3 ), were synthesized, and their curing behavior and heat resistance were investigated. Difunctional benzoxazine 2 was cured at a temperature higher than the mono- and trifunctional benzoxazines 1 and 3 . The weight of the cured resin, poly(2 ), obtained from 2, was maintained at a higher temperature than either poly(1 ) or poly(3 ), obtained from 1 and 3 . This stability is presumably due to the molecular arrangement of poly(2 ), which is more regulated than that of poly(1 ) or poly(3 ), as supported by DFT calculations, XRD and density measurements. The cured resins adsorbed CO2 in the order of poly(1 ) < poly(2 ) < poly(3 ).